Role of Social Networks in Raising the Level of Self-Care of Pregnant Women - Deimazar, Ghasem; Kahouei, Mehdi; Rahmanian, Mozhgan; Motamednejad, Neda; Mehrabi, Parnian (Journal of Liaquat University of Medical & Health Sciences, 2019)
OBJECTIVES: To introduce the role of online social networks in raising the level of self-care of pregnant women. METHODOLOGY: This was a observational cross-sectional study. Four hundred and four pregnant women were estimated as sample using the sample size estimation of Cochran (confidence level of 95%), among the ones who referred to outpatient clinic and inpatients of Amir Almomenin hospital of Semnan, Iran. The questionnaire used in this study included three sections and the authors developed it after reviewing the related literatures. The questionnaire was tested as pilot on 28 pregnant women which were randomly chosen from Amir Almomenin hospital. RESULTS: Our Study showed that the highest average score of using the pregnant women from social networks was to use the experience of pregnant women who had a child aged 3.46±1.33 and also related to the concerns of the pregnant women due to differences in the information of physicians and social network users 2.67±1.34. The findings showed that there were significant relationships between some of the individual characteristics of pregnant women and their use of social networks (P<0.01). CONCLUSION: According to the findings of this research, electronic communication between pregnant women and the clinical staff (midwives and physicians) through social media requires the promotion of social network use by this group. It thus seems necessary to encourage physicians to use social media to properly monitor their patients’ maternal and fetal health.